Factors associated with malaria treatment failures in Ibadan (2005)
This study aims to find out factors associated with anti-malaria drug resistance in some selected areas in Ibadan. One thousand one hundred and two subjects were interviewed viewed using a semi structured questionnaire. Respondents were put into two different groups (high and low resistant areas). The result revealed a high level of drug use for treating malaria particularly chloroquine and sulfadoxinepyrimethamine (“Fansidar”). The Results also showed that the two groups were not significantly different with respect to clearance of infection, but there was a significant difference between clearance of infection and whether or not the respondent completed the course of treatment in each group (P<0.05). When both groups were combined, the Mantel-Haenszel test showed that the response difference between the two groups was significant. (OR= 3.44 (Cl= 1.8 to 6.51) i.e those that completed the treatment were 3 times more likely to have their infection cleared than those that did not complete the treatment. A significant finding was that non-compliance with treatment was a major factor associated with treatment failure. The prevalence of drug resistance was a little higher in the high resistant group compared to the low resistant group but this difference was not statistically significant. These results underscore the need for adequate health education about the treatment of malaria and the importance of compliance in this community.